2023
DOI: 10.1007/s11136-023-03466-2
|View full text |Cite
|
Sign up to set email alerts
|

How do older adults receiving aged care services understand and respond to the EQ-5D-5L? A think-aloud study in residential care

Abstract: Purpose The EQ-5D-5L is a preference-based instrument for measuring and valuing health-related quality of life (HRQoL). The EQ-5D-5L has been used extensively in economic evaluation, including in aged care. However, older adults’ understanding of the EQ-5D-5L has not been comprehensively investigated to date. This research aimed to assess older adults’ understanding of the EQ-5D-5L using a think-aloud protocol with two cognition groups: no cognitive impairment and mild/moderate cognitive impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This evidence suggests that more residents should be able to self-report using the QOL-ACC than when using other quality of life instruments typically used with this population. For example, a think aloud study using the EQ-5D-5 L identified substantial issues in older adults understanding of the items and response categories [ 44 ] More research is needed on a larger sample to confirm these initial QOL-ACC findings to support providers choice and justification of self or proxy report for residents with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests that more residents should be able to self-report using the QOL-ACC than when using other quality of life instruments typically used with this population. For example, a think aloud study using the EQ-5D-5 L identified substantial issues in older adults understanding of the items and response categories [ 44 ] More research is needed on a larger sample to confirm these initial QOL-ACC findings to support providers choice and justification of self or proxy report for residents with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Lay et al. 40 stated that older adults with and without cognitive impairments reported the most response issues of the EQ‐5D‐5L in usual activities and self‐care, which may be interpreted as less appropriate in that sample. A further study concluded, that people consider their ability to do housework and leisure to be most closely related to usual activities, which indicates a wide range of interpretation.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Further, the raters could differ in their comprehension and interpretation of the questionnaire items, affecting the responses and supporting disagreements. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations